JOFIL: Johar leaf extract lotion as antifungal / Dwiqi Ibnu Khoirin ... [et al.] - Ibnu Khoirin, Dwiqi; Fadillah, Imelda Septia; Fadila, Farah Nur; Barqil Ilmi, Fahin Aruman; Hidayati, Fauziana Arkhima; Putra, Afuan Fajrian (2024)
Sometimes, it is enough to make humans busy, so they often forget to pay attention to cleanliness and health. Cleanliness and personal health are the primary keys to maintaining a healthy body and minimising the risk of transmission of dangerous diseases. Lack of personal hygiene can cause various serious diseases, including skin diseases caused by multiple viruses, bacteria, and fungi that multiply on the skin's surface. Thus, we are interested in making innovations to solve these problems by creating products such as "JOFIL” (Johar Leaf Lotion), which can be used as topical antifungal drugs. This product's content of johar leaves serves as an inhibitor of fungal growth and bacteria that can interfere with human health. The product is practical and easy to use. Users regularly apply it to the area of infection twice daily so that fungal growth and bacteria can be stopped and the skin is free from itching.